Encoding of spatial patterns using electrotactile stimulation via a multi‐pad electrode placed on the torso. Issue 10 (27th June 2022) - Jure, Fabricio A.; Spaich, Erika G.; Malešević, Jovana; Kostić, Miloš; Štrbac, Matija; Došen, Strahinja
Abstract: Background: Tactile stimulation can be used to convey information to a user in different scenarios while avoiding overloading other senses. Tactile messages can be transmitted as spatial patterns, potentially allowing for a high information throughput. The aim of the present study was to design and test different encoding schemes to determine the best approach for conveying spatial patterns. Methods: Encoding schemes with simultaneous (SIM) and sequential pad activation (SEQ) were evaluated, including four SEQ variants designed to potentially facilitate the recognition. In SEQ‐col and SEQ‐row, the column and row of the activated pad were signified using different frequencies, while SEQ‐all and SEQ‐all‐fast included the activation of all pads where those belonging to the pattern were indicated by changes in frequency (ON pads). The success rate (SR) of the pattern identification and the response time were quantified in 15 participants who recognized 20 patterns delivered through a 3 × 2 pad matrix placed on the lateral torso. Results: SIM was not a feasible method to present the patterns (median, 15%; IQR, 5%). The SR improved with SEQ (median, 60%; IQR, 20%) and further increased with additional cues, particularly with SEQ‐row (median, 78.3%; IQR, 23.3%) and SEQ‐all (median, 96.7%; IQR, 5%). Importantly, the stimulation time of SEQ‐all could be decreased without a substantial drop in accuracy (SEQ‐all‐fast: median, 89.2%; IQR, 19.2%). Conclusions: The spatiotemporal stimulation with sequential activation of all pads (SEQ‐all) seems to be the method of choice when conveying tactile messages as spatial patterns. This is an important outcome for increasing the information bandwidth of communication through the tactile channel. Abstract : Recognition of tactile spatial patterns delivered using a multi‐pad electrode to the lateral torso can be significantly improved by activating the pads sequentially. The performance can be further increased by adding a frequency cue to denote row or column, while the best results are achieved using combined spatiotemporal and frequency modulation.